KOMPONEN DAN JENIS-JENIS TINDAK TUTUR "STAF RECEPTION" DENGAN TAMU JEPANG DI SAKURA BALI ESTHETICS SPA - Dewa Gede, Anggri Pinandika (Humanis; Volume 12. No.2. Agustus 2015, 2015)
This thesis entitled “Components and Types of Speech Acts of The Reception Staffs with Japanese Guests at Sakura Bali Esthetics Spa”, using the theory proposed by Searle (1969). The data collection method and technique used in this study is observation methods. The analysis method used in this study is padan extralingual methods. And the presentation of data analysis using informal methods. Components of speech acts reception staff when communicating with Japanese guests mostly useds locutions act which serves to convey greetings, care-product description which shows service hospitality and payment transactions. Meaning illocutions and perlocutions used to make an offer or an increase in sales. The types of speech acts reception staff at Sakura Esthetics Spa Bali is dominated by direct speech acts and indirect speech acts. Type of direct speech acts used by reception staff to inform notify, and ask something to the guests. Type of indirect speech acts used to offer and in the process buying and selling spa care-product. The impression of speech act is conveyed indirectly to affect the opponent speech.
Keywords: Pragmatics, locution, ilocution, and perlocution, the types of speech acts.